Diversification of STEM (Science, Technology, Engineering, and Mathematics) Integrated Learning Models as an Innovation in Vocational Learning in the Merdeka Belajar Era - Muhammad Idris Effendi; Hakkun Elmunsyah; Widiyanti; Lailatul Nurjanah; Fadliyanti Firdausia; Fahru Riza (Didaktika: Jurnal Kependidikan, 2024)
This research presents a study on the implementation of STEM (Science, Technology, Engineering, and Mathematics) education in the context of vocational education in the era of independent learning, emphasizing self-directed learning. Through qualitative descriptive methods and literature review analysis, this study highlights the transformation of conventional teaching paradigms into more dynamic, creative approaches focused on developing students' problem-solving skills. The research findings confirm the improvement of students' competencies, including planning, design, reflection, construction, and modification aspects of STEM projects. Another significant discovery is that integrating STEM with other teaching models such as Project-Based Learning (PjBL) or Problem-Based Learning (PBL) effectively enhances students' critical thinking, creativity, communication, and collaboration skills regardless of gender. In conclusion, the implementation of STEM education not only prepares vocational education students to face the challenges of the 21st century and the era of independent learning but also stimulates students' interest and engagement in learning, promotes inclusivity, and enhances the overall quality of education.